'5T' Approach to Governance Transformation: Finding a Doctrinal Basis for Further Research. (June 2023) - Mishra, Santap Sanhari
Public management reform is a continuum that accommodates various reform approaches with the passage of time. The basic objective of such approaches is to transform governance by enabling the swifter and better delivery of public services to citizens. In 2019, the government of Odisha, a state in India, introduced teamwork, transparency, technology and a time-bound programme for transforming governance (popularly called the 5Ts), aiming to provide good governance to its citizens. This article searches for a proper theory to fit this popular practice of the 5Ts approach to governance and also proposes models for carrying out further research.